Material Adverse Change: An Alternative Solution to Suspension of the Debt Payment. - Suwinto Johan (Humaniora, 2020)
The research aimed to provide alternative solutions with Material Adverse Change (MAC) before reaching the suspension of the debt payment obligation stage. The pandemic situation had caused many companies to experience difficulties in fulfilling their obligations, including payment obligations or debts to suppliers and creditors. If there were circumstances where the company could not fulfill its obligations, then the creditor would be able to collect through debt-restructuring to bankruptcy. The restructuring was carried out through the suspension of the debt payment obligation (Penundaan Kewajiban Pembayaran Utang/PKPU). The research used normative juridical methods. It focused on credit and financing transactions between companies and creditors, both banking or finance companies. The research concludes that before the suspension of a debt payment obligation, companies and creditors should negotiate based on MAC before reaching a lawsuit. In the MAC, there is an explicit clause, and it is agreed by both parties, then the creditor should acknowledge the company’s actual condition.